A comparative photoluminescence study on Mn-Free GaAs/AlAs and Mn-containing Ga1-xMnxAs/AlAs quantum wells (QWs) grown on various orientations by MBE. Issue 3 (22nd January 2016) - Gunes, M.; Erken, O.; Gumus, C.; Yalaz, E.; Pesen, E.; Ukelge, M. O.; Arpapay, B.; Serincan, U.; Taykurt Daday, M.; Galvão Gobato, Y.; Henini, M.
Abstract: Optical properties of diluted magnetic semiconductor Ga0.999 Mn0.001 As/AlAs quantum well structures grown on (1 0 0 ), (1 1 0), (3 1 1)B and (4 1 1)B by molecular beam epitaxy are reported. Temperature-dependent spectral photoluminescence (PL) measurement was performed at temperatures between 15 and 300 K. The PL measurements showed that band gap of the alloy decreases with increasing lattice temperature regardless the growth orientations. S-shaped temperature dependence has been observed in the samples grown on (1 0 0), (3 1 1)B, (4 1 1)B orientations. PL emission energy is fitted with Varshni and Bose–Einstein Approximation to determine Debye temperature ( β ), (ΘE ) and thermal expansion coefficient ( α ), the exciton–phonon coupling strength ( a B ) .